Complicating, considering, and connecting music education - Richerme, Lauren Kapalka (Counterpoints (Bloomington, Ind.), 2020)
In Complicating, Considering, and Connecting Music Education, Lauren Kapalka Richerme proposes a poststructuralist-inspired philosophy of music education. Complicating current conceptions of self, other, and place, Richerme emphasizes the embodied, emotional, and social aspects of humanity. She also examines intersections between local and global music making. Next, Richerme explores the ethical implications of considering multiple viewpoints and imagining who music makers might become. Ultimately, she offers that music education is good for facilitating differing connections with one's self and multiple environments. Throughout the text, she also integrates the writings of Gilles Deleuze and Félix Guattari with narrative philosophy and personal narratives. By highlighting the processes of complicating, considering, and connecting, Richerme challenges the standardization and career-centric rationales that ground contemporary music education policy and practice to better welcome diversity.--